Several mode-locked pulses generation and transmission over soliton based optical transmission link - Amiri, I.S.; Alavi, S.E. (Institute of Advanced Engineering and Science, 2016)
A soliton-based optical communication system is presented to generate and transmits several mode locked laser pulses (generated by fiber laser setup) over 50 km fiber and 120 m wireless link. The passive mode-locking feature of the laser system proposed in this paper is based on nonlinear polarization rotation evolution.